An Application of Expert System For Diagnozing Endoparsitism Gastrointestinal Disease In Livestock Animals - Rusdi Efendi; Sri Hartati (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2007)
AbstractThe goal of this research is to make an expert system as a tool for diagnozing endoparsitism gastrointestinal disease for cows and sheep. The knowledge base of the system has been acquired from some interviews with some doctors from the internal diseases animal's unit at Animal's Hospital, Gadjah Mada University Jogjakarta, some text books, journals, and research papers. The inference machine of the system uses Forward Chaining and uncertainty data methods using Dempster-Shafer Theory.The system has a consultation session with an interactive dialog that can be used by the users. A user gives information such as user's data, and answers the questions about the endoparsitism gastrointestinal symptoms that might be had by his animal. From the answers, the system computes the possibility of the animal to suffer from endoparsitism gastrointestinal, informs the life cycle parasites, and suggests a therapy for it.Keywords : Expert System, diagnoze, endoparsitism gastrointestinal disease, Forward chaining method, Dempster-Shafer Teary